2018
DOI: 10.1103/physreva.97.033623
|View full text |Cite
|
Sign up to set email alerts
|

Efimov states near a Feshbach resonance and the limits of van der Waals universality at finite background scattering length

Abstract: We calculate the spectrum of three-body Efimov bound states near a Feshbach resonance within a model which accounts both for the finite range of interactions and the presence of background scattering. The latter may be due to direct interactions in an open channel or a second overlapping Feshbach resonance. It is found that background scattering gives rise to substantial changes in the trimer spectrum as a function of the detuning away from a Feshbach resonance, in particular in the regime where the background… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 83 publications
5
25
0
Order By: Relevance
“…However, experimental results urged the theory to reinterpret the 3BP. Indeed, it was shown that this universality stems from the fact that atoms interact through a van der Waals potential which suppresses the probability to find the particles at short distances from each other [22][23][24][25][26][27]. The break-down of this universality has been predicted to occur only near closed-channel-dominated Feshbach resonances [28][29][30] which was confirmed in a recent experiment [18].The Efimov-van der Waals universality is well established for a < 0.…”
mentioning
confidence: 81%
“…However, experimental results urged the theory to reinterpret the 3BP. Indeed, it was shown that this universality stems from the fact that atoms interact through a van der Waals potential which suppresses the probability to find the particles at short distances from each other [22][23][24][25][26][27]. The break-down of this universality has been predicted to occur only near closed-channel-dominated Feshbach resonances [28][29][30] which was confirmed in a recent experiment [18].The Efimov-van der Waals universality is well established for a < 0.…”
mentioning
confidence: 81%
“…Finally, the interaction of the impurity with the bath of fermions is described by the third term, where the impurityψ σ and a host atomψ are converted into the molecular stateφ. Here the form factor χ(r) determines the shape of the atom-to-molecule coupling and we choose χ(r) = e −r/ρ /4πρ 2 r where the range ρ is determined by the van-der-Waals length [84,85].…”
Section: Anderson-fano Modelmentioning
confidence: 99%
“…Calculations from theories based on a single-channel van der Waals model confirmed this vdW universality for broad Feshbach resonances [26,27,30,41,42]. In recent studies, the observed nonuniversal Efimov ground state locations further confirm that the vdW universality of 3BP is valid only for broad Feshbach resonances [25,43,44]. For heteronuclear systems, i.e.…”
Section: Introductionmentioning
confidence: 66%